(untitled)
In this paper, we concern the divergence Kohn-Laplace equation _i = 1^n _j = 1^n ( X_j^*(a^ij X_iu) + Y_j^*(b^ij Y_iu) ) + Tu = f - _i = 1^n ( X_i^*f^i + Y_i^*g^i ) with bounded coefficients on the Heisenberg group H ^n, where X_1, …, X_n,Y_1, …, Y_n and T are real smooth vector fields defined in a bounded region Ω H^n. The local maximum principle of weak solutions to the equation is established. The oscillation properties of the weak solutions are studied and then the Hölder regularity and weak Harnack inequality of the weak solutions are proved. , number=3, journal=Journal of Mathematical Study, year=2020, month=May, pages=265–296